2014
DOI: 10.1155/2014/136031
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Silicone Oil as a Long-Term Endotamponade Agent for Complicated Retinal Detachments

Abstract: We retrospectively evaluated a heavy silicone oil (HSO) as a long-term intraocular endotamponade agent to treat complicated RD by inferior PVR in 25 eyes of 25 patients. Patients underwent PPV and injection of Oxane HD as an internal tamponade agent. A comparison of preoperative and postoperative BCVA at month 1, month 6, and last visit was made in the group in which HSO was removed and in the group in which HSO was not removed. Statistical calculations were performed using the Wilcoxon test. The HSO was remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
2
19
5
Order By: Relevance
“…From the Silicone Study Group, a higher retinal redetachment rate after SO removal in patients with PVR-C3 and higher has also been reported [45]. In addition, several reports about surgery outcomes from complex retinal detachment surgery using heavy SO have shown success rates ranging between 39 and 92%, with different number of surgeries being required and a high incidence of complications being reported [42, 4649]. Mancino et al recently reported 100 and 90.4% success rate of vitrectomy with inferior 180° peripheral retinectomy and SO tamponade in subgroups of patients with recurent retinal detachment and PVR grade C after failed primary scleral buckle surgery and PPV, respectively [50].…”
Section: Discussionmentioning
confidence: 99%
“…From the Silicone Study Group, a higher retinal redetachment rate after SO removal in patients with PVR-C3 and higher has also been reported [45]. In addition, several reports about surgery outcomes from complex retinal detachment surgery using heavy SO have shown success rates ranging between 39 and 92%, with different number of surgeries being required and a high incidence of complications being reported [42, 4649]. Mancino et al recently reported 100 and 90.4% success rate of vitrectomy with inferior 180° peripheral retinectomy and SO tamponade in subgroups of patients with recurent retinal detachment and PVR grade C after failed primary scleral buckle surgery and PPV, respectively [50].…”
Section: Discussionmentioning
confidence: 99%
“…It is known to be a very effective long-term solution in cases that underwent pars plana vitrectomy to stabilize complex retinal detachments. Still, despite constant improvement, the relative tolerability and safety profile obliges to SIO removal as soon as the retina has been stabilized or SIO related complications appear [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our final 81.3% success rate for primary reattachment at least 6 months after Densiron ® 68 removal is consistent with the results of other studies. 19,20 Only 48% of patients had anatomical success after Oxane ® HD removal. This suggests that Densiron ® 68 provided better support for the inferior retina than Oxane ® HD.…”
Section: Discussionmentioning
confidence: 99%